Risk management in the internationalization of small and medium-sized Spanish companies - Ana Cruz González Calzadilla; María Segovia Villarreal; Juan Manuel Ramón Jerónimo; Raquel Flórez López (Journal of Risk and Financial Management, 2022)
The aim of this study is to analyze how Spanish small and medium-sized enterprises (hereinafter SMEs) manage risks derived from internationalization to improve performance. For this purpose, a case study was elaborated to understand the different risk management strategies used by Spanish SMEs in order to improve performance. Data were collected through sixteen semi-structured interviews. Findings suggest that although the internationalization process involves risk, SMEs, despite their size, can develop a proper risk management which leads to improve performance. Additionally, it is suggested that internationalization risks are not an impediment for SMEs to become involved in international activity, but that it is the way they manage them which makes SMEs improve their performance. Furthermore, the internationalization strategy becomes more efficient when a differentiation and innovation strategy are followed simultaneously.
Keywords: 650; SMEs; risk management; differentiation; internationalization; risks